Annual Plan 1993-94 - Planning Commission (Planning Commission, 1993)
During the Seventh Plan period (1985-86 to 1989-90) the economy grew at an annual average rate of 5.8%. Annual average rate of inflation was at the moderate level of 7 to 8%. Dollar value of exports had grown al an annual average rate of 11.5%. Though the annual growth rate of imports was lower at 9.4%, the level of imports was comparatively higher than exports. As a result, the balance of payments situation deteriorated slowly.
Government of India Planning Commission
Government of India Planning Commission